Analisis Manfaat Kaki Palsu (Prothesa) Terhadap Aktivitas Fisik Pada Kaum Difabel (Tuna Daksa) Di Paguyuban Penyandang Cacat Jasmani Dan Wirausaha - Raden Adhi Warsyah Saputra; Ida Wahyuni; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2014)
Disabled is a disorder or disability that caused disruption the body function, this disorder can be happen at limb bones, body muscles, or at the joints, both congenital or got by accident or disease. The using of tools such as prostheses used to support the daily activities of the disabled people so they can live independently and not depend on others. The aim of this research is to analyze the benefit of prosthetic limbs with the physical activity of the diffable people in association of physical disabilities and entrepreneurial. This research used qualitative research by observational approach and descriptive analytic. The informants of this research were the disabled people who using prothesa in association of physical disabilities and entrepreneurial. The number of informants in this research is 8 informants. This research was done by in-depth interview and observation. Validity test was done by triangulation and technique. The result of this research shows that all of the informants have the motivation in the use of prostheses which is to become rise up so they can fulfilled their daily needs. All of the informants had known the function of the use of prostheses with the physical activity and seven of them knew the types of treatment that done to the prostheses. All of the informants can do physical activities such self-care, mobility but about take the stairs they still need a little to middle help, depends on the type of amputation. All of informants said that they can do physical activities just like the normal people but in longer frequency because they need to adjust their balance from the body movement. It’s recommended for the informants to do treatment towards their prostheses such as giving oil at the joints, add more rubber at their footware so it won’t be slippery and do cleaning so the prostheses will keep clean